Mapping, Characterization, and Expression Analysis of the SM-20 Human Homologue, C1orf12, and Identification of a Novel Related Gene, SCAND2 - Dupuy, Denis; Aubert, Incarnation; Dupérat, Véronique Guyonnet; Petit, Joëlle; Taine, Laurence; Stef, Marianne; Bloch, Bertrand; Arveiler, Benoı̂t (Genomics (San Diego, Calif.), 2000)
Major psychosis was shown to segregate with a balanced translocation (1q42.1; 11q14.3) in a multigenerational family. This study describes the identification of a human SM-20 homologue gene that lies at about 400 kb on the centromeric side of the 1q42.1 breakpoint. The full-length cDNA sequence and gene structure were determined. Expression analysis was performed, showing high expression levels in skeletal and cardiac muscles; in the central nervous system, expression was restricted to dopaminergic neurons and spinal motoneurons. A second gene displaying high sequence similarity with SM-20 was also identified by BLAST. This gene, located on chromosome 15, is likely to have evolved by retroposition of SM-20 mRNA and an exon-shuffling mechanism. It encodes a 306-amino-acid protein harboring strong homology with an N-terminal motif found in some zinc-finger proteins. This gene was named SCAND2 (SCAN domain-containing 2).